The Office of William Tite (1798-1873): Architecture at the Start of the Railway Age - Mike Chrimes (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article looks at how William Tite’s office practice developed in the context of the financial and professional world in which he lived and worked. The office supported Tite’s activities for 50 years from c. 1823 until his death in 1873. He was one of the most successful English architects of the nineteenth century in terms of wealth and general reputation. His principal office was located in the City of London, close to his commercial clients. With the arrival of the railway age, these clients enabled Tite to become a well-known figure in the provision of professional architectural and valuation services to railway companies. Like most practices of the time, his office staff was small and he was only able to provide services by delegating or passing on work to other architects and surveyors, and by establishing sub-offices where necessary. Thus, in the 1840s, he had offices of some form in France, Carlisle, Edinburgh and Perth. His busy schedule meant he frequently provided sketches whilst in the midst of site visits, and he therefore relied on his office staff to provide finished drawings. Ultimately, he had a number of partners who carried on his practice for a further generation.